Pengaruh Fasilitas Kantor Terhadap Kinerja Pegawai Di Bagian SDM dan Sekretariat PT Madu Baru Yogyakarta - Ervil Revilda Khotimah, Astrin; Wening Budiningrum, Endah (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
This study aims to determine the effect of office facilities on employee performance in the HR and Secretariat section of PT Madu Baru Yogyakarta. The type of research used in this research is descriptive quantitative analysis. The data used in this study are primary and secondary data. The sample in this study were 31 respondents. This research was conducted at the PT Madu Baru Yogyakarta Office, HR and Secretariat. This study uses simple regression analysis, t-test and using data sourced from respondents and observations. Test results test results based on the significant value test with the provisions that if the sig value is <0.05 obtained a sig value of 0.000 which means <0.05. In the summary model, the result of R square results show the results of 0.658 or 65.8%, which means that variable Office Facilities variable affects variable Y by 65.8%. The t test obtained the results of t count of 7.473> t table 2.04523 means that variables Office Facilities and Employee Performance are significant. Thus it can be concluded that the results of the simple regression test and the t test from the research show that the facilities of the school are significant and t test from the study found that office facilities affect employee performance in the HR and Secretariat section of PT